"Les gens de cette place": Oblates and the Evolving Concept of Métis at Île-à-Crosse, 1845-1898 - Foran, Timothy P. (2011)
This dissertation examines the construction and evolution of categories of indigeneity within the context of the Oblate (Roman Catholic) apostolate at Île-à-Crosse in present-day north-western Saskatchewan between 1845 and 1898. While focusing on one central mission station, this study illuminates broad historical processes that informed Oblate perceptions and impelled their evolution over a fifty-three-year period. In particular, this study illuminates processes that shaped Oblate concepts of sauvage and métis. It does this through a qualitative analysis of missionary correspondence, mission records and published reports. In the process, this dissertation challenges the orthodox notion that Oblate commentators simply discovered and described a singular, empirically existing and readily identifiable Métis population. Rather, this dissertation contends that Oblates played an important role in the conceptual production of les métis.